(untitled) (Journal of Academic Research, 2025)
This study aimed to show the impact of the change in owned capital and deposits on the earning capacity of the United Bank for Trade and Investment in Libya during (2021-2022). The study used four quantitative measures to determine the strength of the bank’s owned capital, namely the ratio of owned capital to total assets, the ratio of owned capital to risky assets, the ratio of owned capital to total deposits, and the ratio of owned capital to total loans. The impact of the change in owned capital and deposits on the bank’s earning capacity was shown by dividing the rate of return on owned capital by the rate of return on investment. The quantitative analytical approach was used, which is described as relying on conducting a financial analysis of the bank’s balance sheets and financial statements during (2021-2022).One of the most important results reached by the study is that the results of the analysis of the four indicators for calculating the adequacy or strength of owned capital all indicate a lower ability of the owned capital balance to face losses, whether in total assets, in risky assets, or in loans, but Only deposits increased by a small percentage in 2022 compared to 2021,and therefore the bank in 2022 was not better than it was in 2021, meaning that the capital owned by the bank is not moving towards the better.The increase achieved in the total of both owned capital and deposits has negatively affected the bank’s revenue generating capacity.